Development Fragility Curves of R/C Building by Linear Regression - دبول, غنوه (Tishreen University Journal -Engineering Sciences Series,, 2023)
This paper presents a study of R/C buildings, where the buildings had dual systems and frame systems where the participations of frames to resist the shear force are 28.% These building are designed by Syrian Code and in this study it will studying by nonlinear time History analysis to Development Fragility Curves by Linear Regression. The results of study showed the property damage in studying building for inter story drift d.